Environmental Governance in Latin America - De Castro, Fabio; Hogenboom, Barbara; Baud, Michiel (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book is open access under a CC-BY license. The multiple purposes of nature - livelihood for communities, revenues for states, commodities for companies, and biodiversity for conservationists - have turned environmental governance in Latin America into a highly contested arena. In such a resource-rich region, unequal power relations, conflicting priorities, and trade-offs among multiple goals have led to a myriad of contrasting initiatives that are reshaping social relations and rural territories. This edited collection addresses these tensions by unpacking environmental governance as a complex process of formulating and contesting values, procedures and practices shaping the access, control and use of natural resources. Contributors from various fields address the challenges, limitations, and possibilities for a more sustainable, equal, and fair development. In this book, environmental governance is seen as an overarching concept defining the dynamic and multi-layered repertoire of society-nature interactions, where images of nature and discourses on the use of natural resources are mediated by contextual processes at multiple scales.